Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Sense of belonging and social climate in an official language minority post-secondary setting - Penner, Kailey; de Moissac, Danielle; Rocque, Rhéa; Giasson, Florette; Prada, Kevin; Brochu, Paul (Canadian Journal of Higher Education, 2021)
Perceived sense of belonging and positive social climate on campus are crucial elements for post-secondary students, as they contribute to academic achievement, positive mental health, and help-seeking. Few studies have explored post-secondary students’ sense of belonging and perceptions of social climate in an official language minority campus, which attract Canadian-born francophones, anglophones who pursue higher education in their second language, and francophone international students. With declining student mental health and greater ethnolinguistic diversity of post-secondary students on Canadian campuses, this important study aims to explore francophone students’ perceived sense of belonging and social climate on campus. In total, 35 students from different ethnolinguistic backgrounds took part in focus groups or individual interviews. Domestic students with French as their first language more often reported positive social climate on campus and a sense of belonging, in contrast to international students and students with French as a second language. A common obstacle to connecting with others was language insecurity in one of the official languages, as both are currently used on campus. Universities hosting students of multiple linguistic diversities should provide courses and campus events to stimulate intercultural knowledge and dialogue.

Étude sur la santé mentale et les comportements à risque des jeunes adultes - De Moissac, Danielle; Gueye, Ndeye Rokhaya; Plourde, Vikcie; Arseneau, Jolyève; Levesque, Émilie; Corriveau, Hélène; Goguen, Cynthia; Giasson, Florette (Université de Moncton et Université de Saint-Boniface, 2024)
Les jeunes adultes en milieu postsecondaire vivent une transition de vie importante : une plus grande indépendance, de nouvelles relations interpersonnelles et sociales, des prises de décisions déterminantes et des responsabilités importantes qui peuvent être difficiles à gérer, pour certaines personnes. Ces nombreux changements peuvent déstabiliser un sentiment de bien-être et occasionner des troubles de santé mentale, des comportements à risque et des difficultés académiques. Un sentiment d’appartenance à un groupe identitaire est généralement associé à un sentiment de bien-être psychologique, des relations interpersonnelles satisfaisantes et moins de comportements à risque. Les milieux postsecondaires sont des lieux privilégiés pour le développement de ce sentiment d’appartenance, particulièrement dans les CLOSM. (...) L’objectif principal de l’étude est de mieux connaître l’état de santé mentale et les comportements à risque de la population étudiante en milieux postsecondaires dans les communautés de langue officielle en situation minoritaire dans deux provinces canadiennes. Au moment de la collecte de données, la plupart des activités et des cours en présentiel étaient revenus à un état similaire au contexte prépandémique. Ces objectifs permettront à l’équipe de recherche de produire des données probantes qui informeront les parties prenantes (population étudiante, corps professoral, personnel des services à l’effectif étudiant et personnel administratif) des besoins de la population étudiante. Une stratégie de mobilisation des connaissances accompagne cette étude.